Platelet Indices and CXCL12 Levels in Patients with Intrauterine Growth Restriction - Shahgheibi S; Mardani R; Babaei E; Mardani P; Rezaie M; Farhadifar F; Roshani D; Naqshbandi M; Jalili A (Dove Medical Press, 2020)
Shole Shahgheibi,1,* Roya Mardani,1,* Erfan Babaei,2 Parastoo Mardani,3 Masomeh Rezaie,1 Fariba Farhadifar,1 Daem Roshani,2 Mobin Naqshbandi,2 Ali Jalili2 1Deparment of Obstetrics and Gynecology, Faculty of Medicine, Kurdistan University of Medical Sciences, Sanandaj, Iran; 2Cancer & Immunology Research Center, Research Institute for Health Development, Kurdistan University of Medical Sciences, Sanandaj, Iran; 3Department of Biology, Faculty of Sciences, Payame Noor University, Sanandaj, Iran*These authors contributed equally to this workCorrespondence: Ali JaliliCancer & Immunology Research Center, Research Institute for Health Development, Kurdistan University of Medical Sciences, Sanandaj, IranTel +98 9 183771862Email Ali130@gmail.comBackground: Intrauterine growth restriction (IUGR) is a multifactorial condition, and the precise mechanism is still unknown. In the current study, we aimed to determine the relationship between the platelet (PLT) indices and CXC12 levels in patients with IUGR.Patients and Materials: In this study, 36 patients with IUGR and 36 healthy pregnant mothers were enrolled as the case and control groups, respectively. Gestational age for both groups was between 24 and 40 years. Blood samples were taken, and platelet indices were examined by a full-diff cell counter. Serum levels of CXCL12 were measured by ELISA, and the data were analyzed using an independent Student’s t-test.Results: In this study, we observed that the mean value of PLT count (154.3 ± 50 vs 236 ± 36) and plateletcrit (0.124 ± 0.038 vs 0.178 ± 0.021) were significantly lower in the case than the control group. In contrast, the mean platelet volume (7.94 ± 0.55 vs 7.62 ± 0.53) and platelet distribution width (17.57 ± 0.7 vs 16.96 ± 0.59) were significantly higher in the case than the control group. More importantly, we found that the serum levels of CXCL12 were significantly higher (5.3 ng/mL± 3.1 vs 2.8 ± 1.6) in the patients compared to the pregnancy controls.Conclusion: Our data show that platelet indices are changed in IUGR, and the levels of circulating CXCL12 are increased in patients with IUGR. These findings provide a base for further studies to better defining the pathophysiology of IUGR.Keywords: platelets, SDF-1, intrauterine growth restriction, CXCL12